1991
DOI: 10.1213/00000539-199108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Actions of Desflurane in Normocarbic Volunteers

Abstract: The cardiovascular actions of three concentrations of desflurane (formerly I-653), a new inhalation anesthetic, were examined in 12 unrnedicated normocapnic, normothermic male volunteers. We compared the effects of 0.83, 1.24, and 1.66 MAC desflurane with measurements obtained while the same men were conscious. Desflurane caused a dose-dependent increase in right-heart filling pressure and a decrease in systemic vascular resistance and mean systemic arterial blood pressure. As measured by echocardiography, lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
4
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 7 publications
5
52
4
4
Order By: Relevance
“…This study also showed that the decrease in cardiac index was significantly greater if propofol was used instead of isoflurane. We preferred desflurane as an inhalation agent due to its hemodynamic stabilizing effect which was demonstrated in numerous studies (Pagel et al 1991;Weiskopf et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that the decrease in cardiac index was significantly greater if propofol was used instead of isoflurane. We preferred desflurane as an inhalation agent due to its hemodynamic stabilizing effect which was demonstrated in numerous studies (Pagel et al 1991;Weiskopf et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Cardiovascular Effects Inhalation anesthetics produce a dose-dependent reduction in mean arterial pressure (MAP). Again, nitrous oxide is the exception 3,7,8 (see Table 3). Agents differ in terms of the specific physiologic parameter that they target, for example, heart rate, myocardial contractility, and systemic vascular resistance ( SVR ).…”
Section: Respiratory Effectsmentioning
confidence: 99%
“…General anesthesia results in significant changes in the microvasculature involving primarily changes in the diameters of the arterioles and venules and combined changes in arterial pressure and the cardiac output [4,5]. The peripheral vascular effects of the anesthetics may influence the choice of anesthesia and may alter the results of experimental investigations performed in anesthetized animals.…”
Section: Discussionmentioning
confidence: 99%
“…Microcirculatory parameters are altered by the most anaesthetics agent used for induction and during the anaesthesia process. These parameters have effects on the vasoactivity [1][2][3], blood pressure [4,5] cardiac output [6] and vascular resistance [7].…”
Section: Introductionmentioning
confidence: 99%